The The Effect of Energy Security on Economic Growth in ASEAN During 2000–2020 - Kusumawardani, Deni; Agusti, Kemala Sari (International Journal of Energy Economics and Policy, 2024)
Energy is an important input for economic growth. The increase in non-renewable energy consumption has an impact on energy insecurity. This study aims to calculate energy security and analyze its effect on ASEAN economic growth during the 2000–2020 period. The method used in this study is the Principal Component Analysis to calculate energy security and the Feasible Generalized Least Square panel data regression to analyze its effect on economic growth. The authors use four dimensions to build an energy security index, namely availability, accessibility, acceptability, and efficiency. Several variables are included in the model, are capital, labor, trade, and world oil price. The results of this study indicate that the index and dimensions of energy security have a positive influence on ASEAN economic growth, except for the efficiency dimension. Capital. employment, trade, and oil prices have a positive influence on ASEAN economic growth. Regional Governments need to reduce the gap in the electrification ratio in several countries and build energy infrastructure. The government also needs to increase the application of energy diversification, increase renewable energy production and the need to pay more attention to environmental policies in economic activities.